2015
DOI: 10.1002/art.39231
|View full text |Cite
|
Sign up to set email alerts
|

A BAFF Receptor His159Tyr Mutation in Sjögren's Syndrome–Related Lymphoproliferation

Abstract: Objective To study the prevalence, clinical associations, and functional implications of the His159Tyr mutation of the BAFF receptor (BAFF‐R) in patients with Sjögren's syndrome (SS). Methods The BAFF‐R His159Tyr mutation was evaluated using polymerase chain reaction (PCR)–based assays in 247 patients with SS (of whom 70 had SS complicated by lymphoma [SS‐lymphoma]), 145 with systemic lupus erythematosus (SLE), and 101 with rheumatoid arthritis (RA), as well as 180 healthy controls. Real‐time PCR and Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 41 publications
3
45
2
Order By: Relevance
“…It is of interest that these adverse predictors are present early, as soon as the diagnosis of SS is made, implying that a distinct genetic background might determine low and high risk SS subtypes. In support of this hypothesis, genetic alterations related to B cell activation, such as variants of B-cell activating factor, a survival factor for B lymphocytes, [14] tumor necrosis factor alpha-induced protein 3, a gatekeeper of NFKB activation, [15] and the His159Tyr of the B-cell activating factor receptor previously shown to enhance alternate NFKB signaling [46,47] and immunoglobulin production, [46] are implicated in the pathogenesis of SS MALT lymphoma. [47] Other molecules associated with B lymphocytes proliferation and organization in lymphoid tissues, such as Fms-like tyrosine kinase 3 ligand [48] and chemokine C-X-C motif ligand 13, [49] have also been proposed as serum biomarkers of lymphoma in the setting of SS.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that these adverse predictors are present early, as soon as the diagnosis of SS is made, implying that a distinct genetic background might determine low and high risk SS subtypes. In support of this hypothesis, genetic alterations related to B cell activation, such as variants of B-cell activating factor, a survival factor for B lymphocytes, [14] tumor necrosis factor alpha-induced protein 3, a gatekeeper of NFKB activation, [15] and the His159Tyr of the B-cell activating factor receptor previously shown to enhance alternate NFKB signaling [46,47] and immunoglobulin production, [46] are implicated in the pathogenesis of SS MALT lymphoma. [47] Other molecules associated with B lymphocytes proliferation and organization in lymphoid tissues, such as Fms-like tyrosine kinase 3 ligand [48] and chemokine C-X-C motif ligand 13, [49] have also been proposed as serum biomarkers of lymphoma in the setting of SS.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms leading to lymphomagenesis remain unclear, we postulate that the reduced levels of the antiproliferative IFNα in a context of IFNγ-related chronic inflammation could be a major driver of malignant transformation in the setting of SS. On the other hand, it has been been suggested that activation of NFkB signaling pathways -recently shown to be activated in SS- [10], leads to decreased IFNα levels through proteasomal degradation of Interleukin-1 receptor-associated kinase 1 (IRAK1) impairing phosphorylation of the interferon regulatory factor 7 (IRF7), an essential transcription factor for IFNα production [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Clinical, serological and histopathological features such as purpura, salivary gland enlargement, C4 hypocomplementemia, germinal center formation and the presence of interleukin-18 (IL-18) producing macrophages in minor salivary gland (MSG) tissues have been previously associated with lymphoma development in the setting of SS [3-5]. Additionally, mutations of the p53 gene, the presence of the t(14:18) translocations, genetic variants of the B cell activating factor (BAFF) and its receptor, as well as the tumor necrosis factor alpha-induced protein 3 (TNFAIP3) gene have been considered to confer increased risk for lymphoma development [6-10]. …”
Section: Introductionmentioning
confidence: 99%
“…Genetic abnormalities, oncogenetic events, the involvement of NF-kB pathway, of cytokines, growth factors and chemokines [8,44,47,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] and the ongoing expansion in tissue lesions of the same B-cell clone [33], are also linked to the increased risk of lymphoma development or to multistep lymphomagenesis in pSS (reviewed in [86] and in [26]). They include B cell activating factor (BAFF) and Tumor necrosis factor alpha induced protein 3 (TNFAIP3) variants, BAFF receptor His159Tyr mutation, chromosomal translocations and oncogene deregulation, increased serum levels of Fms-related tyrosine kinase 3 ligand (Flt3-L), of C-X-C motif ligand 13 (CXCL13), and high Interferon (IFN) γ/IFNα ratio in minor SG biopsy.…”
Section: Other Risk Factorsmentioning
confidence: 99%